THE EFFECT OF HEAT THERMAL TO THE MECHANICAL PROPERTIES OF AISI 1045 UNDER WATER COOLING MEDIA - Jhonni, Rahman (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2021)
This study was conducted to determine how heat treatment with water cooling media affect the mechanical properties of AISI 1045 Steel. The analysis was carried out by comparing AISI 1045 Steel without heat-treatment and AISI 1045 Steel with heat-treatment at 8000C and 8500C. The results showed that the hardness of AISI 1045 steel increased to 47.95 HRC at 8000C and 53.5 HRC at 8500C, increased from 41.23 HRC for AISI 1045 steel without heat-treatment. Likewise, heat-treatment also increased the strength of AISI 1045 carbon steel from 624.28 MPa to 741.72 MPa at 8000C and 998.61 MPa at 8500C. In addition, the fatigue test also showed an increase in the ductility of AISI 1045 Steel which was subjected to heat-treatment. This can be seen as the number of cycles that occur in the heat-treated material which was higher than that of non-heat-treated material.